2010
DOI: 10.2166/wst.2010.320
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of 2,4-dichlorophenol in a fluidized bed reactor with immobilized Phanerochaete chrysosporium

Abstract: The performance of a fluidized bed reactor using immobilized Phanerochaete chrysosporium to remove 2,4-dichlorophenol (2,4-DCP) from aqueous solution was investigated. The contribution of lignin peroxidase (LiP) and manganese peroxidase (MnP) secreted by Phanerochaete chrysosporium to the 2,4-DCP degradation was examined. Results showed that Lip and Mnp were not essential to 2,4-DCP degradation while their presence enhanced the degradation process and reaction rate. In sequential batch experiment, the bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Li et al showed that a certain pre-exponential phase could be observed, with the duration time estimated to last 72 h [67], whereas Zhang et al reported a 24-hour-long exponential phase [69]. The duration of exponential growth and the inhibition growth phase (4 days, approximately) was confirmed mainly by previous reports, where it was equal to 5-6 days [66,67].…”
Section: Growth Curvementioning
confidence: 85%
See 2 more Smart Citations
“…Li et al showed that a certain pre-exponential phase could be observed, with the duration time estimated to last 72 h [67], whereas Zhang et al reported a 24-hour-long exponential phase [69]. The duration of exponential growth and the inhibition growth phase (4 days, approximately) was confirmed mainly by previous reports, where it was equal to 5-6 days [66,67].…”
Section: Growth Curvementioning
confidence: 85%
“…In contrast, the adaptation and acceleration phases were not very well pronounced, according to results for optimum-growing medium [66,67], cotton stalks [68], or corn-cob extract [66]. Li et al showed that a certain pre-exponential phase could be observed, with the duration time estimated to last 72 h [67], whereas Zhang et al reported a 24-hour-long exponential phase [69]. The duration of exponential growth and the inhibition growth phase (4 days, approximately) was confirmed mainly by previous reports, where it was equal to 5-6 days [66,67].…”
Section: Growth Curvementioning
confidence: 94%
See 1 more Smart Citation
“…It is a plug flow reactor that belongs to the group where back mixing is not present; but in this reactor small amount of back mixing occurs that affects the attributes of the fermentation (Figure 8) [43]. Fluidized-bed bioreactor (Source: [41]).…”
Section: Packed Bed Reactormentioning
confidence: 99%
“…[490][491][492] Another crucial arena is the immobilization of biomaterials onto a sturdier and porous support that has been significantly investigated for varied applications; examples can be found for fungi and microalgae and exploitation for hydrogen production. [493][494][495][496][497] Indeed, immobilized cells have garnered a huge attention since the 1970s, because of their clear merits over dispersed cells. 498 First, the immobilization of native biomaterial improves the physical properties and proposes advanced degree of action.…”
Section: Biomolecule Immobilization On Iron Oxide Nanoparticles Towar...mentioning
confidence: 99%